2010
DOI: 10.1007/s11538-010-9556-x
|View full text |Cite
|
Sign up to set email alerts
|

Polyhedral Geometry of Phylogenetic Rogue Taxa

Abstract: It is well known among phylogeneticists that adding an extra taxon (e.g. species) to a data set can alter the structure of the optimal phylogenetic tree in surprising ways. However, little is known about this "rogue taxon" effect. In this paper we characterize the behavior of balanced minimum evolution (BME) phylogenetics on data sets of this type using tools from polyhedral geometry. First we show that for any distance matrix there exist distances to a "rogue taxon" such that the BME-optimal tree for the data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 33 publications
2
15
0
Order By: Relevance
“…That is, we will show that for every topology of the in-group, there is a set of arbitrarily distant outliers that can lead to this topology when using neighbour joining. These results are similar to those of Cueto and Matsen (2011) for the BME algorithm, though our proof for NJ is independent of theirs and more elementary.…”
Section: Neighbour Joining Is Out-group Volatilesupporting
confidence: 84%
See 1 more Smart Citation
“…That is, we will show that for every topology of the in-group, there is a set of arbitrarily distant outliers that can lead to this topology when using neighbour joining. These results are similar to those of Cueto and Matsen (2011) for the BME algorithm, though our proof for NJ is independent of theirs and more elementary.…”
Section: Neighbour Joining Is Out-group Volatilesupporting
confidence: 84%
“…A related line of work is concerned with properties of consensus functions, which provide a way to summarise the agreement between two or more trees, by Bryant (1997) and Eulenstein (2006), among others. Lastly, our results on the volatility of neighbour joining bear resemblance to the work of Cueto and Matsen (2011) on the BME algorithm. However, our results were obtained independently and we provide simpler proofs.…”
Section: Previous Worksupporting
confidence: 65%
“…Their study indicated that 29% of four taxa phylogenies would be reconstructed differently had a fifth taxa been added. These percentages increased to 50% for five taxa trees and 62% for six taxa trees (Cueto and Matson, 2011). However, Cueto and Matson point out that their estimated rogue frequencies may have been greater given the use of random branch lengths (2011).…”
Section: Introductionmentioning
confidence: 98%
“…They found that the rogue taxa effect was common when the added taxa were chosen without reference to the original tree (arbitrarily) and that the effect worsened as the number of taxa increased (Cueto and Matson, 2011). Their study indicated that 29% of four taxa phylogenies would be reconstructed differently had a fifth taxa been added.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation